Theory for normal state critical Kapitza resistance of 4He - Ferrell, R. A.; Bhattacharjee, J. K.; Mukhin, S. I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
We study a steady state, bearing a heat current, Q0, in the normal state of liquid 4He with constraining geometry, near the lambda point, at temperatures T greater than the lambda temperature, Tlambda. Critical order parameter fluctuations near the boundary are incorporated in the expression for the non-local thermal resistivity. The Kapitza resistance is manifested by the additional temperature rise at the boundary, as compared with the bulk-extrapolated value. Sensitivity of the calculations to the application of the Dirichlet boundary condition is discussed.